Impact of disease duration on functional status of patients with spinocerebellar ataxia type 2 - Thiago R. Padilha Amarante; Sibele Y. M. Takeda; Hélio A. G. Teive; Marise Bueno Zonta (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective: To correlate disease duration in spinocerebellar ataxia type 2 (SCA2) with disease severity, balance and functionality. Method: Sixteen SCA2 patients were analyzed for: disease duration, disease severity (SARA score), balance (Berg balance scale score) and functionality (FIM and Lawton scores). Results: Greater severity was correlated with worse functionality (Lawton: r = −0.0561, FIM: r = −0.6402) and balance (r = −0.7188). Longer disease duration was correlated with greater severity (p = 0.0002) and reduced functionality (FIM: p = 0.005; Lawton: p = 0.0402) and balance (p = 0.0036). A year increase in disease duration corresponded to a 0.8-point increase on the SARA scale, a 1.38-point decrease in FIM score, a 2.30-point decrease on the Berg balance scale and a 0.45-point decrease on the Lawton scale. Conclusion: Longer disease duration in this series of SCA2 patients was correlated with greater disease severity, worse balance and greater functional dependency.